Missed opportunities: The unknown impact of the COVID-19 pandemic on early childhood development in the WHO European region - J.M. White; C.L. Goodfellow; A.O. Adeleke; F.P. Awde; Y.W. Chua; A. Jovic; E. Scott (Public Health in Practice, 2025)
Background: Early childhood experiences can promote or adversely affect children's development and wellbeing with lifelong impact. The COVID-19 pandemic disrupted children's and families' lives worldwide. It is important to understand the effect on early childhood development. We aimed to examine what is known about the impact of the COVID-19 pandemic, and the related public health measures, on young children's development. Study design: We carried out a mixed-method study which included a scoping review of review-level evidence about early childhood development over the course of the pandemic compared to beforehand and a web-based survey of early childhood development data published in the WHO European Region. Methods: A systematic search of three databases was used to identify studies, published in English, up to November 2024. Findings were synthesised narratively by developmental domain. A web-based search was used to identify, routinely collected, national surveillance child development data in the WHO European Region. To illustrate the potential role of routine surveillance in the timely identification of developmental concerns, trend data from Scotland was examined. Results: Seven reviews met the inclusion criteria. Most studies examined young children's mental health, while others assessed language development, mother-child bonding, and broader developmental outcomes. Findings were inconsistent, with some studies reporting adverse effects, with others finding no significant changes. There were significant gaps in the availability of national surveillance child development data in WHO European Region countries. Scottish surveillance data identified increases in developmental concerns, which affected disadvantaged groups more. Conclusions: The available evidence about the effect of the COVID-19 pandemic, and related public health measures, on early childhood development is limited and inconclusive. Strengthening data collection and reporting across the WHO European Region is essential for timely and accurate assessment of developmental outcomes and to guide policy development.